2023
DOI: 10.21660/2023.111.4003
|View full text |Cite
|
Sign up to set email alerts
|

Edge Detection Technique for Simultaneous Measurement of Total Suspended Solids and Turbidity

Rijal Hakiki

Abstract: APHA Standard methods 2130B and 2540D have proven valid and reliable methods to determine turbidity and total suspended solids (TSS). However, both methods have drawbacks and limitations. Carcinogenicity of formazin, inconsistency in preparation, and interference are the primary concerns in turbidity measurement. Equipment complexity, working steps, and measurement time are primary concerns in TSS measurement. The edge detection technique (EDT) is an alternative to overcome the drawbacks and limitations. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Digital image processing techniques analyze the gray levels in water images to estimate turbidity levels. For instance, studies have demonstrated how image pixels correlate with water turbidity [15][16][17]. These methods, however, also face challenges such as sensitivity to lighting conditions and image quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital image processing techniques analyze the gray levels in water images to estimate turbidity levels. For instance, studies have demonstrated how image pixels correlate with water turbidity [15][16][17]. These methods, however, also face challenges such as sensitivity to lighting conditions and image quality.…”
Section: Introductionmentioning
confidence: 99%
“…This methodology was adopted to maintain a controlled environment and eliminate variables that could introduce noise and optical aberrations. In this way, we ensure that the optimization algorithms focus on the nature of the database, which consists of black points (suspended solids) on a white background, analogous to liquid samples with suspended solids as referred as referred in articles [15][16][17]27]. The aim of this research is to identify the most suitable optimizer based on the nature of the database and to provide additional information about the performance of each optimizer.…”
Section: Introductionmentioning
confidence: 99%